The relationship between work-life conflict, workforce agility, and subjective well-being among remote employees: The underlying mechanism of job stress - Sari, Ega Yugesti; Widyowati, Arini; Arendse, Najuwa (Psikohumaniora: Jurnal Penelitian Psikologi, 2025)
While remote working conditions became more prominent post COVID-19, they have influenced a shift in the subjective well-being (SWB) of remote employees. The impact of the associated job stress has been underexplored in Indonesia. Drawing on the job demands-resources model, this research investigates the underlying mechanisms of job stress in explaining the relationships between work-life conflict, workforce agility, and SWB among remote employees. A total of 350 permanent employees who work fulltime remotely in several organization in Indonesia (65.7% women, M-age = 26.19 years; SD = 3.66) participated in the study. Data were collected using scales measuring work-life conflict, workforce agility, SWB and job stress, distributed online via Google Forms. The data were analyzed using structural equation modeling (SEM) techniques with the IBM SPSS AMOS program. The results showed that work-life conflict and workforce agility were associated with subjective well-being ( β = -.32 and .79, p < .001; respectively). Furthermore, job stress fully explains the relationship between work-life conflict and subjective well-being (CI -.46 – -.12) and partially explains the association between workforce agility and subjective well-being (CI .62 – .87). The findings have implications for how organizations and counsellors can assist remote employees in enhancing their well-being by managing their stress, promoting workforce agility, and overcoming work-life conflicts.